Innovative strategies implemented by universities to support medical radiation science students during the COVID‐19 pandemic - Michala Short; Eileen Giles (Journal of Medical Radiation Sciences, 2021)
The global COVID‐19 pandemic has impacted all facets of life. In medical radiation science (MRS) education, the effects on continuity of learning were felt by educators, students and clinical supervisors both nationally and internationally. The focus of this commentary is on the common elements that impacted MRS students, specifically related to cancelled clinical placements and the interruption to their academic progress at university. An outline is provided of some innovative strategies implemented by universities and clinical departments to support students’ academic progress, continuity of clinical experiences, their transition from students to practitioners and overall strategies to support student wellbeing. The recent published literature illustrates novel responses to shared challenges faced, and an opportunity to learn from collective experiences.